Design of DOB-based riveting force controller for dual-machine horizontal drilling and riveting system. (November 2019) - Liu, Yi; Fang, Qiang; Zhao, Anan; Yang, Feng; Wang, Hongsheng; Ke, Yinglin
Abstract: A dual-machine horizontal automatic drilling and riveting system for aircraft panel assembly is presented in this paper. Two cooperative machines are adopted, like a two-robot system, to achieve the unobstructed workspace, so it can be applied in an efficient assembly line. Different from the current deign wisdom to ensuring the riveting accuracy by increasing the machine stiffness, which detrimentally results in higher masses to be moved and sophisticated reinforcements being used, this paper proposes a disturbance observer (DOB) based design method of riveting force controller for adaptive riveting with high accuracy driven heads, reducing the dependence of automatic riveting on high stiffness of machine. This method simplifies the force-induced deformation error compensation problem to a force control problem, which has rarely been studied before in literature. The separate layout leads to weak machine stiffness in the whole workspace and the stiffness varies with machine pose greatly, which makes it difficult to establish an accurate force-induced deformation error compensation model. To make the riveting machine precisely generate the desired force under such stiffness-varying conditions, a robust control algorithm is designed: the disturbance observer is introduced to address the robust stability against model parameter variance caused by the change of system stiffness with pose, and the feedforward controller can achieve the high-bandwidth force control to ensure the riveting efficiency. The model identification experiments are carried out for different machine stiffness. Validation riveting experiments have been conducted to verify the proposed controller on the dual-machine riveting system. The results show that, compared with previous displacement control, the proposed force controller can ensure the consistency of driven heads through accurate force control.